Disconnection More Problematic for Adolescent Self-Esteem than Heavy Social Media Use: Evidence from Access Inequalities and Restrictive Media Parenting in Rural America. (April 2023) - Hampton, Keith N.; Shin, Inyoung
Some argue that social media use displaces time that adolescents spend with friends and family and is therefore associated with lower psychological well-being. They reason that young people who experience "disconnection, " because their parents actively restrict media use, or they have limited material access to the Internet, are better protected from psychological harm. Prior research has misspecified and exaggerated the magnitude of the relationship between screen time and adolescent psychological well-being. If the harm associated with heavy (excessive) or even average use of new media has been overstated, then the recommendation of disconnection may also be problematic. New media use is heavily integrated into youth culture and sociality, restrictive media parenting practices or digital inequalities may rob adolescents of experiences that would otherwise be protective of self-esteem. We conducted a survey of rural adolescents, who are more likely to experience disconnection at home because of a lack of physical availability of broadband, not simply affordability. Based on that survey, we find that a negative relationship between screen time and lower self-esteem is eclipsed by a more substantive, negative relationship to inequalities in material access to the Internet and restrictive mediation of media by parents. Findings show that new media use does not substantively displace time spent socializing with family and friends and in other social activities (e.g., volunteering). Omitting the supportive, indirect relationship between time on social media and self-esteem, through time spent socializing, exaggerates the negative relationship between social media use and adolescent well-being for girls, and for boys, misspecified the direction of the relationship. Adolescents, who experience heavy restrictive mediation of media by parents or have limited Internet access at home, tend to report substantively lower self-esteem than heavy users of any new media.